FMR1 expression in human granulosa cells and variable ovarian response: control by epigenetic mechanisms - Rehnitz, Julia; Youness, Berthe; Nguyen, Xuan Phuoc; Dietrich, Jens Erik; Rösner, Sabine; Messmer, Birgitta; Strowitzki, Thomas; Vogt, Peter H. (Molecular human reproduction, 2021)
In humans, FMR1 (fragile X mental retardation 1) is strongly expressed in granulosa cells (GCs) of the female germline and apparently controls efficiency of folliculogenesis. Major control mechanism(s) of the gene transcription rate seem to be based on the rate of CpG-methylation along the CpG island promoter. Conducting CpG-methylation-specific bisulfite-treated PCR assays and subsequent sequence analyses of both gene alleles, revealed three variably methylated CpG domains (FMR1-VMR (variably methylated region) 1, -2, -3) and one completely unmethylated CpG-region (FMR1-UMR) in this extended FMR1-promoter-region. FMR1-UMR in the core promoter was exclusively present only in female GCs, suggesting expression from both gene alleles, i.e., escaping the female-specific X-inactivation mechanism for the second gene allele. Screening for putative target sites of transcription factors binding with CpG methylation dependence, we identified a target site for the transcriptional activator E2F1 in FMR1-VMR3. Using specific electrophoretic mobility shift assays, we found E2F1 binding efficiency to be dependent on CpG-site methylation in its target sequence. Comparative analysis of these CpGs revealed that CpG 94-methylation in primary GCs of women with normal and reduced efficiency of folliculogenesis statistically significant differences. We therefore conclude that E2F1 binding to FMR1-VMR3 in human GCs is part of an epigenetic mechanism regulating the efficiency of human folliculogenesis. Our data indicate that epigenetic mechanisms may control GC FMR1-expression rates.
Gesehen am 14.06.2021